The Influence Of Compensation And Benefits, Work Environment, And Employee Demographics On Employee Performance Mediated By Motivation In Paper Manufacturing Companies - Tutut Arif Rachman; Agung Winarno; Ely Siswanto (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of compensation and benefits, work environment, and employee demographics on employee performance mediated by motivation in quantitative manufacturing companies using a survey method. The research population was all employees, with a sample of 104 employees selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study's results indicate that compensation and benefits have a positive and significant impact on employee performance and motivation. The work environment has a positive and significant effect on motivation, but it does not have a direct effect on employee performance. Employee demographics have no significant effect on employee motivation or performance. Motivation has a positive and significant effect on employee performance and has been shown to mediate the relationship between compensation and benefits, as well as the work environment, on employee performance. This research provides practical implications for company management in improving employee performance through improved compensation systems, conducive work environments, and increased work motivation.